Pemanfaatan Penggunaan Darah Donor Yang Telah Kadaluwarsa Untuk Pembuatan Agar Darah Pada Pertumbuhan Staphylococcus aureus - Rr. Irma Dewi Novita; Indah Febrianti (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
The use of media so that sheep's blood for the growth of Staphylococcus aureus bacteria is still difficult to get the sheep's blood. Therefore, a way to find alternatives to sheep blood is sought, namely by using donor blood that has expired. In this study using blood agar media using blood donors and blood agar media using sheep blood as a control. Using a blood donor with a presentation of 4% and 5% of the colony diameter, zone of hemolysis, the color of the colony of Staphylococcus aureus is almost the same as supported grown in 4% sheep blood agar media. While 6%, 7% and 8% blood donors are not supported for the growth of Staphylococcus aureus because the hemolysis zone and colony color are different from controls using sheep blood agar media